Identificación de zonas de riesgo por inundación mediante un modelo hidrológico y uso de herramientas SIG en un segmento de la región de La Mojana, Colombia (2023)
The region of La Mojana, belonging to the Momposina Depression, is constantly subject to flooding caused by the overflowing of the Cauca, Magdalena and San Jorge rivers, which is a deteriorating factor for land communication, development of agricultural activities and cultivable areas, since this region is occupied by approximately 437,000 inhabitants, 47.7% of the rural area and the rest is located in areas near the shore of the swampy system that makes up this region.